2013
DOI: 10.1002/app.39396
|View full text |Cite
|
Sign up to set email alerts
|

Improved chemical resistance of ink‐jet printed micropatterns on glass by using dual‐functional compositions

Abstract: UV curable and UV/moisture dual‐functional oligomers were synthesized by grafting trimethoxysilane and methacrylate segments on the polyimide oligomer chains. These oligomers and a dual‐functional monomer were used as ink compositions to enhance the chemical resistance of ink‐jet printed LCD color filter micropatterns, without sacrificing jetting performance. The molecular structure and molecular weight of the oligomers were altered to adjust the solubility of oligomer in monomers, together with jetting trajec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The rheology of jet inks can be adjusted by changing the surfactants and monomers to achieve good jetting directionality, uniform droplet size, and excellent wetting on the substrate [ 165 ]. UV-curable [ 166 , 167 ] and dual curable monomers and oligomers [ 168 , 169 ] can be used in the compositions of ink-jet fluids. Wang et al [ 170 ] reported the ink-jet printing of colloidal photonic crystal (PC) microdots that demonstrate the fastest response (about 1.2 s) to water vapor.…”
Section: Stimuli-responsive Hydrogels Patterningmentioning
confidence: 99%
“…The rheology of jet inks can be adjusted by changing the surfactants and monomers to achieve good jetting directionality, uniform droplet size, and excellent wetting on the substrate [ 165 ]. UV-curable [ 166 , 167 ] and dual curable monomers and oligomers [ 168 , 169 ] can be used in the compositions of ink-jet fluids. Wang et al [ 170 ] reported the ink-jet printing of colloidal photonic crystal (PC) microdots that demonstrate the fastest response (about 1.2 s) to water vapor.…”
Section: Stimuli-responsive Hydrogels Patterningmentioning
confidence: 99%
“…To overcome this drawback, the dual curing system should be introduced. Several researches indicate that the dual‐curable oligomers show the better thermostability, higher crosslinking density, and chemical resistance, thus it is essential to synthesize a thermostable resin with excellent adhesion on solder resist ink.…”
Section: Introductionmentioning
confidence: 99%
“…Their group synthesized a kind of linear and star‐like polymer–silica hybrid oligomers and study the advantages of its hybrid curing system, presenting better thermostability by the characterization of thermogravimetric analysis (TGA). Furthermore, their group synthesized the UV and moisture polyimide oligomer chains grafting the trimethoxysilane and methacrylate segments for inkjet printing, improving the chemical resistance of the printed pattern on glass.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, printing technology has attracted significant attention because patterning methods for wet materials can be an alternative to conventional fabrication processes for electronic devices while providing high throughput resulting in relatively low-cost manufacturing. Among the many printing methods available, including screen printing, inkjet printing [1], flexographic printing [2,3], gravure printing [4,5], and reverse offset printing [6][7][8], microcontact printing (µCP) is one of the most promising candidate methods for printed electronics because of its prominent capability of high-resolution patterning [9]. While µCP [10,11] was invented and developed as a chemical patterning method [12,13] in the past two decades, this technique is also attractive because of its capability to pattern various types of materials such as colloidal crystals [14,15], quantum dots [16], and catalytic colloids for electroless deposition [17].…”
Section: Introductionmentioning
confidence: 99%